External Reporting Analysis of Hospital Information System (SIRS-Revision VI) at Hospital - Antik Pujihastuti; Trismianto Asmo Sutrisno; Diah Rochani (Poltekkes Kemenkes Semarang, 2025)
Hospital Information System (HIS) is an external report that must be fulfilled by every hospital to the Health Efforts Development of the Ministry of Health periodically according to the reporting deadline. The data source used comes from the Hospital Management Information System which is an application that is integrated into all health services so that it can be used as a source of hospital reporting. One of its uses is as external hospital reporting data. This hospital reporting is one of the indicators for measuring the achievement of health services for the community. The method used is descriptive analysis to measure the achievement and obstacles faced in processing external reporting data. This measurement is to obtain an overview of the implementation of external hospital reporting through SIMRS which is used to compile the SIRS Revision VI report in meeting the needs of the Ministry of Health periodically. The results of the identification of types and periods where reporting is carried out through reporting applications including the Hospital Emergency Incident System, Online Hospital Information System and Hospital Information System Revision VI.